Universal Signals of Humor in the Live Adaptation and Cartoon of Mr. Bean - Pramayanti, Mona; Anjani, Sinta Laura; Az-Zahra, Jeyhan Brilliantica; Danyanindhitya, Tyaskita (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study aims to examine the universal humor signals in the Mr. Bean series, both in the live-action and cartoon versions. The main focus of this research is how humor is conveyed through non-verbal communication such as facial expressions, body movements, and comical situations without dialogue. This research employs a qualitative descriptive method with a semiotic approach and uses encryption and relevance theories as the analytical framework. The data were taken from selected episodes in both versions and analyzed using Spradley’s four-stage analysis: domain, taxonomy, componential, and cultural theme The results of this study show that both versions rely on non-verbal humor signals, but with different approaches. The live-action version tends to display a more realistic style and subtler expressions, while the cartoon version uses exaggerated movements and expressions. These stylistic differences show that the visual medium affects how humor is delivered. Nevertheless, both formats remain widely accessible due to their use of humor signals that are understandable across cultures and languages